Determinants of healthcare access among older adults in Mandalay Region, Myanmar: A cross-sectional analysis: 10.55131/jphd/2026/240215 - Aung, Yadanar; Sutthida Chuanwan; Pojjana Hunchangsith; Pimonpan Isarabhakdi; Yothin Sawangdee; Marc Völker (Journal of Public Health and Development, 2026)
Population ageing is accelerating globally and poses significant challenges to health systems, especially in low- and middle-income countries. In Myanmar, access to healthcare services among older persons is under-researched, particularly in the Mandalay Region. This study investigates healthcare utilization patterns and associated socio-demographic factors among older adults in three high ageing-index districts: Meikhtila, Nyaung U, and Myingyan. A cross-sectional analytical design was employed, with data collected from June to August 2021. Results from a multivariate logistic regression revealed that older adults living in rural areas, those with moderate ability to perform daily activities, and those experiencing hearing difficulties were more likely to use public hospitals. In contrast, residents of Myingyan District were less likely to access public health facilities. Use of private hospitals was more common among older adults with moderate self-rated health and those residing in Myingyan. However, individuals with moderate functional ability and those with vision difficulties were significantly less likely to use private hospitals. Utilization of charity clinics was higher among older adults who were employed, including unpaid family workers, and among those who required regular follow-up care or had vision impairments. Conversely, those living in rural areas and individuals from wealthier households were less likely to use charity clinics. These findings highlight the complex and uneven patterns of healthcare access among older persons in Myanmar. They underscore the importance of addressing socio-demographic disparities—particularly in rural areas and among those with physical or sensory limitations—to promote equitable and effective healthcare delivery for an ageing population.